Respuesta :
Answer: y = -1
Step-by-step:
-8y + 1 = -9y
Subtract 1 from both sides
-8y = -9y-1
Add 9y to both sides to isolate y
y = -1
Step-by-step:
-8y + 1 = -9y
Subtract 1 from both sides
-8y = -9y-1
Add 9y to both sides to isolate y
y = -1
Simplifying
8y + -1 = 9y
Reorder the terms:
-1 + 8y = 9y
Solving
-1 + 8y = 9y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-9y' to each side of the equation.
-1 + 8y + -9y = 9y + -9y
Combine like terms: 8y + -9y = -1y
-1 + -1y = 9y + -9y
Combine like terms: 9y + -9y = 0
-1 + -1y = 0
Add '1' to each side of the equation.
-1 + 1 + -1y = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -1y = 0 + 1
-1y = 0 + 1
Combine like terms: 0 + 1 = 1
-1y = 1
Divide each side by '-1'.
y = -1
Simplifying
y = -1
8y + -1 = 9y
Reorder the terms:
-1 + 8y = 9y
Solving
-1 + 8y = 9y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-9y' to each side of the equation.
-1 + 8y + -9y = 9y + -9y
Combine like terms: 8y + -9y = -1y
-1 + -1y = 9y + -9y
Combine like terms: 9y + -9y = 0
-1 + -1y = 0
Add '1' to each side of the equation.
-1 + 1 + -1y = 0 + 1
Combine like terms: -1 + 1 = 0
0 + -1y = 0 + 1
-1y = 0 + 1
Combine like terms: 0 + 1 = 1
-1y = 1
Divide each side by '-1'.
y = -1
Simplifying
y = -1